Penggunaan Metode Technology Acceptance Model (TAM) dalam Analisis Sistem Informasi Alista (Application of Logistic and Supply Telkom Akses) - Ida Ayu Putu Ayunda Aprilia Sugiantari; Ni Luh Ayu Widiasih; I Made Agus Oka Gunawan; Gede Indrawan (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2023)
PT Telkom Akses Denpasar employees are assigned to provide and prepare materials in limited quantities and time. To be fulfilled, employees do work quickly including coordination, procurement, production, product supply, including daily administration and processing information from technicians to customers to make it easier to use the Alista application. Is the perception of interface design, system ease, system acceptance attitude, behavior of using the system measured by how much influence on the real condition of the use of the system that is trusted by employees. The method used to measure the results of research using TAM. Research sample of 78 employees. Based on the analysis results it is known that 35.2% of the four independent variables namely interface design, ease of system, attitude of system acceptance, behavior of system usage affects the real conditions of the use of information systems. The results of the respondents' scores were obtained from the results of a questionnaire from all respondents towards the variable of the question studied, the results of the TAM in the percentage of 44% of respondents' answers on average strongly agreed and 55% of respondents' answers agreed.